2015
DOI: 10.1053/j.gastro.2015.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Effects of Withdrawal of Immunomodulators or Biologic Agents From Patients With Inflammatory Bowel Disease

Abstract: Little is known about the optimal duration of therapy with an anti-tumor necrosis factor (TNF) agent and/or an immunomodulator for patients with inflammatory bowel disease (IBD). We performed a systematic search of the literature to identify studies reporting after de-escalation (drug cessation or dose reduction) of anti-TNF agents and/or immunomodulators in patients in remission from IBD. Studies were reviewed according to the type of IBD and drug. Rates of relapse, factors associated with relapse, and respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(181 citation statements)
references
References 85 publications
(219 reference statements)
5
161
0
15
Order By: Relevance
“…9,10,[13][14][15] Few studies reported on the long-term outcome of patients after IFX withdrawal when in clinical remission. A Danish retrospective observational study reported a low rate of remission (12%) ten years after the last IFX infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10,[13][14][15] Few studies reported on the long-term outcome of patients after IFX withdrawal when in clinical remission. A Danish retrospective observational study reported a low rate of remission (12%) ten years after the last IFX infusion.…”
Section: Discussionmentioning
confidence: 99%
“…longer-term data are still missing. 10 The aim of the present study was to describe the long-term results of the STORI trial and to identify predictors of poor outcomes.…”
Section: Commentmentioning
confidence: 99%
“…In patients who are refractory to conventional treatments, anti-tumour necrosis factor-alpha (anti-TNF)  biologics are effective at inducing clinical response, clinical remission and endoscopic remission 4. There has been a significant amount of research conducted on the impact of discontinuing immunomodulators (ie, azathioprine, 6-mercaptopurine) and biologics on clinical outcomes in IBD due to their cost and side effects 5. However, after a patient with UC requires escalation to biologics, the benefit of continuing or withdrawing 5-ASA is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Other trials outlined the role of concomitant therapy in reducing immunogenicity [68,72]. The decision to withdraw a drug should be made on individual basis, balancing several factors [73,74]. A summary of the key aspects of de-escalating therapy in patients treated with anti-TNF is shown in table 4.…”
Section: Primary Non-responsementioning
confidence: 99%